Determining the coating speed limitations for organic photovoltaic inks - Jakubka, Florian; Heyder, Madeleine; Kaschta, Joachim; Machui, Florian; Brabec, Christoph (Solar Energy Materials and Solar Cells, 2013)
To determine the output capability of present organic photovoltaic (OPV) materials, it is important to know the theoretical maximum coating speeds of the used semiconductor formulations. Here, we present a comprehensive investigation of the coating stability window of several prototype organic semiconductor inks relevant for organic solar cells. The coating stability window was first determined experimentally by a sheet to sheet coater at velocities of up to 10 m/min. A numerical simulation model based on the "Coating Window Suite 2010" software was established to give insight into the coating stability limitations at higher coating velocities. An analysis of PEDOT:PSS [poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate)] in a water/isopropyl alcohol mixture as well as P3HT:PCBM [poly(3-hexylthiophene-2,5-diyl):Phenyl-C61-butyric acid methyl ester] in chlorobenzene, o-xylene and tetrahydronaphthalene showed the possibility of coating speeds up to 60 m/min. The simulation further revealed the maximum coating head distances for a given wet film thickness. Finally, we show a solar-cell with slot-die coated PEDOT:PSS and P3HT:PCBM-layer based on the parameters obtained by the simulated data, which exhibits reasonable performance. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: OPV solar cell; Slot-die coating; Coating speed

Effect of polymer molecular weight and solution parameters on selective dispersion of single-walled carbon nanotubes - Jakubka, Florian; Schießl, Stefan; Martin, Sebastian; Englert, Jan; Hauke, Frank; Hirsch, Andreas; Zaumseil, Jana (ACS Macro Letters, 2012)
The selective dispersion of single-walled carbon nanotube species (n,m) with conjugated polymers such as poly(9,9-dioctylfluorene) (PFO) and poly(9,9-dioctylfluorene-cobenzothiadiazole) (F8BT) in organic solvents depends not only on the type of solvent but also on the molecular weight of the polymer. We find an increasing amount of nanotubes and altered selectivities for dispersions with higher molecular weight polymers. Including the effects of different aromatic solvents, we propose that solution viscosity is one of the factors influencing the apparent selectivity by changing the reaggregation rate of the single-walled carbon nanotubes (SWNT). The type of solvent, polymer molecular weight, concentration, and viscosity should thus be taken into account when screening for new polymers for selective SWNT dispersion. © 2012 American Chemical Society.

Enhanced Ambipolar Charge Injection with Semiconducting Polymer/Carbon Nanotube Thin Films for Light-Emitting Transistors - Gwinner, Michael C.; Jakubka, Florian; Gannott, Florentina; Sirringhaus, Henning; Zaumseil, Jana (ACS nano, 2012)
We investigate the influence of small amounts of semiconducting single-walled carbon nanotubes (SWNTs) dispersed in polyfluorenes such as poly(9,9-di-n-octylfluorene-alt-benzothiadiazole (F8BT) and poly(9,9-dioctylfluorene) (F8) on device characteristics of bottom contact/top gate ambipolar light-emitting field-effect transistors (LEFETs) based on these conjugated polymers. We find that the presence of SWNTs within the semiconducting layer at concentrations below the percolation limit significantly increases both hole and electron injection, even for a large band gap semiconductor like F8, without leading to significant luminescence quenching of the conjugated polymer. As a result of the reduced contact resistance and lower threshold voltages, larger ambipolar currents and thus brighter light emission are observed. We examine possible mechanisms of this effect such as energy level alignment, reduced bulk resistance above the contacts, and field-enhanced injection at the nanotube tips. The observed ambipolar injection improvement is applicable to most conjugated polymers in staggered transistor configurations or similar organic electronic devices where injection barriers are an issue.
EAM Import::2019-03-14

Generalized enhancement of charge injection in bottom contact/top gate polymer field-effect transistors with single-walled carbon nanotubes - Wang, Ming; Jakubka, Florian; Gannott, Florentina; Schweiger, Manuel; Zaumseil, Jana (Organic Electronics, 2014)
We investigate the influence of small amounts of dispersed single-walled carbon nanotubes (SWNTs) on the contact resistance and device characteristics of bottom contact/top gate polymer field-effect transistors (FETs). Five conjugated polymers representing different classes of polymer semiconductors with different HOMO/LUMO levels are employed, namely, polythiophenes (P3HT), polyphenylenevinylenes (MDMO-PPV), polyfluorenes (F8T2), naphthalene-bis(dicarboximide) bithiophene copolymers (P(NDI2OD-T2)), and diketopyrrolo-pyrrole-bithiophene copolymers (DPPT-TT). In all cases the presence of dispersed SWNTs reduces non-ohmic contact resistance and lowers threshold and onset voltages for charge transport. In some cases inherent ambipolar charge transport in conjugated polymers (F8T2 and P(NDI2OD-T2)) is revealed. The concentration of the SWNTs within the semiconducting layer remains below the percolation limit and thus the apparent mobilities and on/off ratios are still determined by the polymer and independent of the specific type of the carbon nanotubes (metallic or semiconducting). The degree of enhancement depends both on the energy level offset between the injecting gold electrode and the HOMO/LUMO level (i.e., Schottky barrier) and the charge carrier mobility of the respective polymer. The simplicity of this injection enhancement method and its broad applicability make it a step toward high performance polymer transistors without injection limitations.
EAM Import::2019-03-13

In Situ Raman Mapping of Charge Carrier Distribution in Electrolyte-Gated Carbon Nanotube Network Field-Effect Transistors - Zaumseil, Jana; Jakubka, Florian; Wang, Ming; Gannott, Florentina (Journal of Physical Chemistry C, 2013)
Solution-processed networks of purely semiconducting single-walled carbon nanotubes (s-SWNTs) can be used to create high-mobility field-effect transistors (FETs) for flexible electronics. In order to optimize network alignment and density, an understanding of carrier distribution within the FET channel is necessary. Here, we used confocal Raman microscopy to investigate charge accumulation and doping in electrolyte-gated FETs with asymmetric layers of only (7,5) nanotubes, that were selected by dispersion in poly(9,9-dioctylfluorene). The nanotube FETs exhibited hole mobilities of up to 7.5 cm2 V–1 s–1 and on/off ratios of 105. All Raman modes decreased in intensity with hole accumulation. The G′-peak and D-peak shifted linearly with negative gate voltages to higher wavenumbers. Using the G′-peak shift, the charge carrier distribution in an operating FET was mapped at different gate and source-drain voltages with high spatial resolution ( 300 nm) and over large areas. With this simple technique, we were able to visualize directly how the assignment of source and drain electrodes determined channel pinch-off and the onset of the saturation regime in FETs with nonuniform carbon nanotube distributions along the channel. In situ Raman mapping could also be applied to other semiconductors that show significant changes in their Raman spectra with doping.
EAM Import::2019-03-13

Mapping Charge-Carrier Density across the p-n Junction in Ambipolar Carbon-Nanotube Networks by Raman Microscopy - Grimm, Stefan; Jakubka, Florian; Schießl, Stefan; Gannott, Florentina; Zaumseil, Jana (Advanced Materials, 2014)
In situ confocal Raman microscopy is used to map the recombination zone (induced p-n junction) in an ambipolar carbon-nanotube-network transistor with high spatial resolution. The shift of the 2D mode (G' mode) depending on hole and electron accumulation serves as a measure for the local charge-carrier density and provides complementary information about charge transport and recombination in ambipolar transistors.
EAM Import::2019-03-12

Mapping charge transport by electroluminescence in chirality-selected carbon nanotube networks - Jakubka, Florian; Backes, Claudia; Gannott, Florentina; Mundloch, Udo; Hauke, Frank; Hirsch, Andreas; Zaumseil, Jana (Acs Nano, 2013)
We demonstrate random network single-walled carbon nanotube (SWNT) field-effect transistors (FETs) in bottom contact/top gate geometry with only five different semiconducting nanotube species that were selected by dispersion with poly(9,9-dioctylfluorene) in toluene. These FETs are highly ambipolar with balanced hole and electron mobilities and emit near-infrared light with narrow peak widths (<40 meV) and good efficiency. We spatially resolve the electroluminescence from the channel region during a gate voltage sweep and can thus trace charge transport paths through the SWNT thin film. A shift of emission intensity to large diameter nanotubes and gate-voltage-dependent photoluminescence quenching of the different nanotube species indicates excitation transfer within the network and preferential charge accumulation on small band gap nanotubes. Apart from applications as near-infrared emitters with selectable emission wavelengths and narrow line widths, these devices will help to understand and model charge transport in realistic carbon nanotube networks. © 2013 American Chemical Society.

Trion Electroluminescence from Semiconducting Carbon Nanotubes - Jakubka, Florian; Grimm, Stefan; Zakharko, Yuriy; Gannott, Florentina; Zaumseil, Jana (ACS nano, 2014)
Near-infrared emission from semiconducting single-walled carbon nanotubes (SWNTs) usually results from radiative relaxation of excitons. By binding an additional electron or hole through chemical or electrochemical doping, charged three-body excitons, so-called trions, are created that emit light at lower energies. The energy difference is large enough to observe weak trion photoluminescence from doped SWNTs even at room temperature. Here, we demonstrate strong trion electroluminescence from electrolyte-gated, light-emitting SWNT transistors with three different polymer-sorted carbon nanotube species, namely, (6,5), (7,5) and (10,5). The red-shifted trion emission is equal to or even stronger than the exciton emission, which is attributed to the high charge carrier density in the transistor channel. The possibility of trions as a radiative relaxation pathway for triplets and dark excitons that are formed in large numbers by electron-hole recombination is discussed. The ratio of trion to exciton emission can be tuned by the applied voltages, enabling voltage-controlled near-infrared light sources with narrow line widths that are solution-processable and operate at low voltages (<3 V).
EAM Import::2019-03-13